GSM based Auto On Main Switch for Power Trips - ANANTHAN, THINESHKUMARAN; Encik Mohd Hakimi bin Zohari, (Progress in Engineering Application and Technology, 2023)
People in Malaysia are particularly vulnerable to adverse weather, such as lightning and thunderstorms where it is required to spend 8 to 12 hours every day in the workplace and less aware about their house. When lightning strikes causes the main switch to power trips to protect the entire house from any mishap and protect the electrical appliances from getting burnt. When blackout happens, some essential gadgets require electrical power to work. The major goal of the project is to assist users with resetting the main switch following a power outage and to notify the users about failure when the system failed to switch ON back the main switch through SMS using GSM technology as well as to monitor the current flow and the ratio of the power trips occurs in a month through IOT in Thingspeak. This device is able to help people who spend the most of their day at work or away from home safeguarding their homes and preserve their important belongings.